Anthocyanin profile of Galician endangered varieties. A tool for varietal selection. (April 2022) - Díaz-Fernández, Ángela; Díaz-Losada, Emilia; Moreno, Daniel; Esperanza Valdés Sánchez, M.
Graphical abstract: Highlights: Polyphenolic fingerprint of 28 minority red grapevine varieties was defined. Anthocyanin profile was a useful element for varietal classification. Anthocyanidins derivatives forms reached 84% discrimination between varieties. Castañal, Ferrón, Espadeiro, and Sousón: promising varieties for red winemaking. Abstract: Polyphenolic characterization of minority red grapevine varieties is a key factor to improve varietal recovery and promotion. This work focuses on determining phenolic family content and anthocyanin (AN) profiles of 28 different red grape varieties during 2018 and 2019 vintages in Galicia (Northwest of the Iberian Peninsula). Most of these varieties are considered "minority varieties" in this region. Additionally, the relationships between the AN groups of compounds were calculated. AN, flavanols, flavonols, hydroxycinnamic acids and stilbenes were extracted, identified, and quantified by High Performance Liquid Chromatography (HPLC). The results show that the phenolic, and more specifically the AN profile, are useful elements for varietal classification. 'Castañal', 'Ferrón', 'Espadeiro' and 'Sousón' stood out because of their content in AN and copigment substances. These varieties differed from the rest of the grape varieties under analysis due to their higher percentages of petunidin and delphinidin derivatives forms. They also had acceptable values of titratable acidity. Since these minority varieties present highly appreciated polyphenolic and acidity characteristics, they should be recommended to be grown in Galicia.